HLA-B*13 :01 Is a Predictive Marker of Dapsone-Induced Severe Cutaneous Adverse Reactions in Thai Patients - Satapornpong, Patompong; Pratoomwun, Jirawat; Rerknimitr, Pawinee; Klaewsongkram, Jettanong; Nakkam, Nontaya; Rungrotmongkol, Thanyada; Konyoung, Parinya; Saksit, Niwat; Mahakkanukrauh, Ajanee; Amornpinyo, Warayuwadee; Khunarkornsiri, Usanee; Tempark, Therdpong; et al. (Frontiers in Immunology, 2021)
HLA-B*13:01 allele has been identified as the genetic determinant of dapsone hypersensitivity syndrome (DHS) among leprosy and non-leprosy patients in several studies. Dapsone hydroxylamine (DDS-NHOH), an active metabolite of dapsone, has been believed to be responsible for DHS. However, studies have not highlighted the importance of other genetic polymorphisms in dapsone-induced severe cutaneous adverse reactions (SCAR). We investigated the association of HLA alleles and cytochrome P450 (CYP) alleles with dapsone-induced SCAR in Thai non-leprosy patients. A prospective cohort study, sixteen Thai patients of dapsone-induced SCARs (5 SJS-TEN and 11 DRESS) and nine Taiwanese patients of dapsone-induced SCARs (2 SJS-TEN and 7 DRESS), 40 dapsone-tolerant controls and 470 general Thai population were enrolled. HLA class I and II alleles were genotyped using polymerase chain reaction-sequence specific oligonucleotides (PCR-SSOs). CYP2C9, CYP2C19, and CYP3A4 genotypes were determined by the TaqMan real-time PCR assay. We performed computational analyses of dapsone and DDS-NHOH interacting with HLA-B*13:01 and HLA-B*13:02 alleles by the molecular docking approach. Among all the HLA alleles, HLA-A*24:07, HLA-C*03:04, HLA-DRB1*15:01, and HLA-DQB1*06:01 showed significant association with dapsone-induced SCARs. However, only HLA-B*13:01 allele was found to be significantly associated with dapsone-induced SCARs (OR = 39.00, 95% CI = 7.67 - 198.21, p = 5.3447x10-7), SJS-TEN (OR = 36.00, 95% CI = 3.19 - 405.89, p = 2.1657x10-3), and DRESS (OR = 40.50, 95% CI = 6.38 – 257.03, p = 1.0784 x 10-5) as compared to dapsone-tolerant controls. Also, HLA-B*13:01 allele was strongly associated with dapsone-induced SCARs in Asians (OR = 36.00, 95% CI = 8.67 - 149.52, p = 2.8068x10-7) and Taiwanese (OR = 31.50, 95% CI = 4.80 - 206.56, p = 2.5519x10-3). Furthermore, dapsone and DDS-NHOH fit within the extra-deep sub pocket of the antigen-binding site of the HLA-B*13:01 allele and change the antigen-recognition site. However, there was no significant association between genetic polymorphism of cytochrome P450 (CYP2C9, CYP2C19 and CYP3A4) and dapsone-induced SCARs (SJS-TEN and DRESS). The results of this study support the specific genotyping of the HLA-B*13:01 allele to avoid dapsone-induced SCARs including SJS-TEN and DRESS before initiating dapsone therapy in the Thai population.